2017
DOI: 10.1007/s00228-017-2292-5
|View full text |Cite
|
Sign up to set email alerts
|

Medical education in pharmacogenomics—results from a survey on pharmacogenetic knowledge in healthcare professionals within the European pharmacogenomics clinical implementation project Ubiquitous Pharmacogenomics (U-PGx)

Abstract: PurposeDue to the diversity within Europe, the implementation of pharmacogenomic testing in clinical practice faces specific challenges. In the context of the European pharmacogenomics implementation project “Ubiquitous Pharmacogenomics” (U-PGx; funded by the European Commission), we studied the current educational background.MethodsWe developed a questionnaire including 29 questions. It was spread out to healthcare professionals working at the future implementation sites (in Austria, Greece, Italy, Netherland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 30 publications
4
77
0
Order By: Relevance
“…All respondents hold a positive attitude when it comes to clinical implementation of PGx, which is in accordance with the findings in other studies such as from the USA, EU and Kuwait …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…All respondents hold a positive attitude when it comes to clinical implementation of PGx, which is in accordance with the findings in other studies such as from the USA, EU and Kuwait …”
Section: Discussionsupporting
confidence: 91%
“…For example in the USA, although the majority of the physicians who responded were aware of the value of PGx, those who have never ordered the test were not planning on doing so in the coming 6 months, mainly due to the lack of information they had about testing and about the genomic markers . More recently in Europe, Just et al . tested the knowledge of physicians and pharmacists concerning their own experience, knowledge about application, and interpretation of PGx testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the European Ubiquitous Pharmacogenomics (U‐PGx) project, we performed a survey asking about general PGx knowledge in clinical practice . This survey was filled out by healthcare professionals and aimed to assess knowledge gaps and training needs that could be addressed by an educational program . The survey revealed that there is a general interest in PGx application.…”
Section: From Science To Patient Carementioning
confidence: 99%